1893 Neb. Consol. Stat. 1231 - (:unkn) unknown (My University, 1893)
Pt. 1, ch. 5, § 5604: Prohibited the concealed carry of a pistol; Bowie-knife, dirk, or any other dangerous weapon. Violators not fined on first offense exceeding one hundred dollars or imprisoned more than thirty days. Second offense not exceeding one hundred dollars or three months imprisonment.
Keywords: CARRY - CONCEALED